Use of qualitative research in World Health Organisation guidelines: a document analysis - Melissa Taylor; Paul Garner; Sandy Oliver; Nicola Desmond (BMC, 2024)
Abstract Background Guidelines depend on effect estimates, usually derived from randomised controlled trials, to inform their decisions. Qualitative research evidence may improve decisions made but where in the process and the methods to do this have not been so clearly established. We sought to describe and appraise how qualitative research has been used to inform World Heath Organization guidance since 2020. Methods We conducted a document analysis of WHO guidelines from 2020 to 2022. We purposely sampled guidelines on the topics of maternal and newborn health (MANH) and infectious diseases, as most of the qualitative synthesis to date has been conducted on these topics, likely representing the 'best case' scenario. We searched the in-built repository feature of the WHO website and used standardised search terms to identify qualitative reporting. Using deductive frameworks, we described how qualitative evidence was used to inform guidelines and appraised the standards of this use. Results Of the 29 guidelines, over half used qualitative research to help guide decisions (18/29). A total of 8 of these used qualitative research to inform the guideline scope, all 18 to inform recommendations, and 1 to inform implementation considerations. All guidelines drew on qualitative evidence syntheses (QES), and five further supplemented this with primary qualitative research. Qualitative findings reported in guidelines were typically descriptive, identifying people's perception of the benefits and harms of interventions or logistical barriers and facilitators to programme success. No guideline provided transparent reporting of how qualitative research was interpreted and weighed used alongside other evidence when informing decisions, and only one guideline reported the inclusion of qualitative methods experts on the panel. Only a few guidelines contextualised their recommendations by indicating which populations and settings qualitative findings could be applied. Conclusions Qualitative research frequently informed WHO guideline decisions particularly in the field of MANH. However, the process often lacked transparency. We identified unmet potential in informing implementation considerations and contextualisation of the recommendations. Use in these areas needs further methods development.